Consonant Changes in Words Borrowed From Sanskrit to Thai and Patani Malay - Songkhla, Angsana Na; Subramaniam, Ilangko (International Journal of Linguistics, 2021)
Southeast Asia was under Indian influence for more than a thousand years so that the traces of Indian civilization can be determined from a lot of evidence. The entry of Indian civilization in this region has shown that Sanskrit has merged with Thai, the national language of Thailand, and Patani Malay, the mother tongue language of Thai Malays who live in the deep south of Thailand. Borrowing is a process of language contact and language change that can happen in all languages and is not limited to borrow in the same language family or the same type of language. All of them belong to different family trees. Sanskrit is a member of the Indo-European language family, whereas the Thai language is accepted to Tai-Kadai and Patani Malay belongs to the Austronesian language family. This study aims to study consonant changes of shared Sanskrit loanwords in Thai and Patani Malay. This research employed qualitative methodology. Data were collected from documentaries. The findings showed that changes in consonant phonemes occurred in both languages according to phonological adaptations such as deletion, insertion, voicing, devoicing, and substitution.